2004
DOI: 10.1002/jmri.20051
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic motion in the sitting and supine positions: Healthy subject study using a vertically open magnetic resonance system

Abstract: Purpose: To determine the postural difference of diaphragmatic motion between the sitting and supine positions. Materials and Methods:A total of 10 healthy men were examined using a vertically open 0.5-T magnetic resonance (MR) system. A total of 40 sequential MR images were obtained in both the sitting and supine positions during two to five respiratory cycles. The diaphragmatic excursions (DEs) were measured on three diaphragmatic points of six sagittal planes for both positions. The differences in DEs betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
37
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 15 publications
6
37
2
Order By: Relevance
“…The observed contributions of particular points (points B, C, and D) to the resultant diaphragm motion (Tables 2 and 4) provide additional, most statistically stringent support for this proposition. The theory of nonuniform recruitment of costal and crural portions of the diaphragm (24) has been previously investigated and reconfirmed (8,23,33,34). The idea that the diaphragm is a functionally dual system where costal and crural portions function mechanically in serial mode, but ventilatory (pneumatically) in parallel mode is confirmed in this study, too.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The observed contributions of particular points (points B, C, and D) to the resultant diaphragm motion (Tables 2 and 4) provide additional, most statistically stringent support for this proposition. The theory of nonuniform recruitment of costal and crural portions of the diaphragm (24) has been previously investigated and reconfirmed (8,23,33,34). The idea that the diaphragm is a functionally dual system where costal and crural portions function mechanically in serial mode, but ventilatory (pneumatically) in parallel mode is confirmed in this study, too.…”
Section: Discussionsupporting
confidence: 66%
“…Similar to Suga et al (33) we could not detect the previously reported finding of asymmetric excursions between hemidiaphragms (8,34,36).…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Only an isolated analysis of the diaphragm was performed, which focused on the diaphragm excursions, due to the limited size of the field of view. 36 Although we have limited the diaphragm excursion measurements to 3 points, this is similar to studies conducted by other authors 36 and can be considered sufficient for this type of study. In addition, the diaphragm excursions alone may not be sufficient to understand all mechanical actions of the rib cage and related musculature.…”
Section: Discussionmentioning
confidence: 62%